Characterization of Polyallylamine/Polystyrene Sulfonate Polyelectrolyte Microcapsules Formed on Solid Cores: Morphology - Kim, Aleksandr L.; Musin, Egor V.; Chebykin, Yuri S.; Tikhonenko, Sergey A. (Polymers, 2024)
Polyelectrolyte microcapsules (PMC) based on polyallylamine and polystyrene sulfonate are utilized in various fields of human activity, including medicine, textiles, and the food industry, among others. However, characteristics such as microcapsule size, shell thickness, and pore size are not sufficiently studied and systematized, even though they determine the possibility of using microcapsules in applied tasks. The aim of this review is to identify general patterns and gaps in the study of the morphology of polyelectrolyte microcapsules obtained by the alternate adsorption of polystyrene sulfonate and polyallylamine on different solid cores. First and foremost, it was found that the morphological change in polyelectrolyte microcapsules formed on different cores exhibits a significant difference in response to varying stimuli. Factors such as ionic strength, the acidity of the medium, and temperature have different effects on the size of the microcapsules, the thickness of their shells, and the number and size of their pores. At present, the morphology of the microcapsules formed on the melamine formaldehyde core has been most studied, while the morphology of microcapsules formed on other types of cores is scarcely studied. In addition, modern methods of nanoscale system analysis will allow for an objective assessment of PMC characteristics and provide a fresh perspective on the subject of research.